Pemanfaatan Penambahan Limbah Inner-Tube Rubber dan Penggunaan Abu Cangkang Kemiri Sebagai Substitusi Filler pada Campuran AC-WC - Lis Ayu Widari; Muthmainnah Muthmainnah; Adzuha Desmi; Syibral Malasyi; Putri Utami (Pusat Riset dan Inovasi Nasional, 2024)
Various problems that occur in asphalt damage in Indonesia have triggered new innovations to deal with existing problems, one of which is by improving the quality of asphalt by adding substances (additives) or substitutions to the aggregate composition. This study aims to determine the utilization of inner tube rubber waste and the use of candlenut shell ash as a substitute filler in the AC-WC mixture. This study is an experimental study. The manufacture of test objects using an AC-WC mixture with a total of 18 test objects was then tested using the Marshall method. The results of this study indicate that the use of inner-tube rubber waste and candlenut shell ash greatly affects the Marshall parameter value. With an Optimum Asphalt Content of 6%, the best variation content was obtained at 3% of inner tire rubber additives and 25% substitution of candlenut shell ash as filler with a density value of 2.341 gr/cm3, VMA 15.50%, VIM 4.36%, VFA 71.87%, stability 1730.79 kg, flow 3.36 mm and MQ 565.01 kg/mm ​​which meets the 2018 Bina Marga Specifications Revision 2.